Antibiotics in the treatment of scrub typhus: A network meta-analysis and cost-effectiveness analysis - Chaoxin Chen; Tingting Chen; Dan Xue; Maobai Liu; Bin Zheng (Journal of Infection in Developing Countries)
Introduction: A pharmacoeconomic analysis model was developed to evaluate the cost-effectiveness of antibiotics from a societal perspective in Korea and China. A network meta-analysis was conducted to evaluate the efficacy of antibiotics.